2016
DOI: 10.4067/s0034-98872016000100006
|View full text |Cite
|
Sign up to set email alerts
|

Características, manejo y evolución intrahospitalaria de usuarios de drogas ilícitas con infarto agudo del miocardio

Abstract: , rAmÓn corbAlán 3,6 . GruPo de estudio multicéntrico del infArto (Gemi) Characteristics, management, and outcomes of illicit drug consumers with acute myocardial infarction (86.3% and 42.5% respectively, p < 0.01). Among consumers, there was a higher percentage of ST segment elevation (85.2% and 67.8% respectively, p < 0.01) and anterior wall AMI (59.9 and 49.5% respectively, p = 0.01). Additionally, they had a higher rate of primary angioplasty (48.8% and 25.5% respectively, p < 0.01). There was no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(29 reference statements)
0
3
0
3
Order By: Relevance
“…Another possible effect is the blocking of sodium/potassium channels, causing cardiovascular changes, which may present increased and prolonged risks when there is an association between cocaine and alcohol. 15 In a review including a range of studies on the effects of the drug, it was found that its frequent use may be strongly associated with an increased risk of acute cardiovascular complications, such as hypertension, coronary aneurysms, arrhythmias and myocardial infarction 14,15,18,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible effect is the blocking of sodium/potassium channels, causing cardiovascular changes, which may present increased and prolonged risks when there is an association between cocaine and alcohol. 15 In a review including a range of studies on the effects of the drug, it was found that its frequent use may be strongly associated with an increased risk of acute cardiovascular complications, such as hypertension, coronary aneurysms, arrhythmias and myocardial infarction 14,15,18,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, among the patients who presented acute myocardial infarction (AMI) and made previous use of cocaine, the highest percentage was of ST-segment elevation acute myocardial infarction (STEMI) and cardiogenic shock, while others manifested ST-segment elevation acute myocardial infarction (STEMI), with heart failure in its presentation 19,24,25 .…”
Section: Methodsmentioning
confidence: 99%
“…A cocaína está associada a diversas doenças cardiovasculares (DCV), como hipertensão, infarto do miocárdio, taquiarritmias, dissecção da aorta, insuficiência cardíaca, vasoespasmo e aterogênese acelerada, decorrente do infarto (9) . O uso abusivo de cocaína é uma das principais demandas pelo serviço público de saúde relacionado aos sintomas cardiovasculares (10) . Entre os atendimentos referentes ao consumo de cocaína, 39,5% dos indivíduos queixam-se de dor torácica aguda e infarto agudo do miocárdio.…”
Section: Introductionunclassified